Vaginal cancer in the fisrt year of life: Case report (Research, Society and Development, 2023)
This study aims to report the case of a 14-year-old patient who sought gynecological outpatient care to determine the integrity of her fertility. Laboratory and imaging tests were requested, which did not reveal any evidence of impaired reproductive functionality. At the age of 1 year and 3 months, the patient experienced vaginal bleeding and was later diagnosed with vaginal cancer. The patient underwent various tests for disease investigation and staging and was referred to a specialized pediatric oncology center due to the complexity of the case. Treatment was conducted based on the histological type and stage of the disease, requiring surgical resection and 5 cycles of chemotherapy. After completing the treatment, the patient remained stable, with developed secondary sexual characteristics and normal test results, showing no signs of impairment in her ovarian reserve.